ANALISIS POTENSI ABNORMAL RETURN POSITIF TERBESAR SAHAM PT.KALBE FARMA SELAMA PANDEMI COVID-19 - Mohammad Arridho Nur Amin (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
This study aims to analyze the largest potential positive abnormal return present in PT. Kalbe Farma during the Covid-19 pandemic. The event study method was used in this study to study indonesia's capital market reactions during the observation period. The observation period was carried out when covid-19 was detected in Indonesia from March 2020 to February 2021 or one month after the implementation of the first covid-19 vaccination in Indonesia. Secondary data used in this study is in the form of daily stock closing stock price data, and daily JCI. The results of the study found that there was an abnormal positive return with the largest value on March 31, 2020 with an abnormal positive return value of 0.12013 and January 11, 2021 with a value of 0.15726